Attributes of Products and Brand Image as a Basis for Purchase Decision - Adriza, Adriza (Opción, 2019)
The purpose of this study is to: determine the perception of the brand hon- ey product attributes Perhutani. Knowing the perception of the brand image of the brand honey products Perhutani. Knowing the consumer decision in buying a brand honey products Perhutani know the influence of product at- tributes and brand image against a decision. The method used is descriptive survey method to describe the behavior of variables and explanatory survey method to test the hypothesis. The type of investigation that is used is the cau- sality hypothesis, namely the type of research that suggested a causal relation- ship between the independent variable, in this case, the product attributes and brand image to the purchasing decision. The unit of analysis of this research is the individual, that is to say, the consumer/buyer of the product at the out- let Perhutani brand HONEY Ahmad Yani and Setiabudi Bandung. Judging from his time horizon, this research is cross-sectional, ie information from the majority of the population (the sample of respondents) was collected directly at the scene empirically, to know the opinion of the majority population of the object being studied. The findings of this study are the performance attrib- utes of the product and the reference groups influence the selling price trend. Performance product mix and the reference group influence on brand image. Performance product mix and the reference group influence on purchase deci- sions. It turned out that the tendency of the selling price and brand image in- fluence on purchase decisions There is a relationship between the selling price trend with the brand image. There is a relationship between the performance of the product mix to the reference group.